2011
DOI: 10.1002/app.34087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of kind and content of organo‐modified clay on properties of PET nanocomposites

Abstract: In this work we report the properties of nanocomposite based on PET with two different samples of organically modified montmorillonites. In particular, we studied the effect of the filler concentration on morphology, rheology, and mechanical performance, focusing our attention on the effect of the degradation phenomena of the clay modifiers. The results indicate that at low clay level the morphology achieved is mainly intercalated. On increasing the filler level, coalescence and/or bad defragmentation phenomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
61
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 33 publications
9
61
1
Order By: Relevance
“…In Figure 2, there are reported the XRD patterns of blends compatibilized with EAA, Figure 2a, HDAA, Figure 2b and EGMA, Figure 2c, prepared by single extrusion (E1), re-extrusion (E2) and extrusion with a masterbatch (MB). As reported in our previous works, the XRD pattern of Cloisite 15A (here not reported for sake of clarity) presents a main broad peak at 2.8° (the position is indicated with dotted vertical lines included in Figure 2a-2c) corresponding to a d-spacing of 3.15 nm [26,[35][36][37]. In Table 3 there are reported the values of 2% corresponding to the main diffraction peak of the XRD patterns and the respective values of interlayer distance calculated by Bragg's law.…”
Section: Results and Discussion 31 X-ray Diffractometry (Xrd)supporting
confidence: 63%
“…In Figure 2, there are reported the XRD patterns of blends compatibilized with EAA, Figure 2a, HDAA, Figure 2b and EGMA, Figure 2c, prepared by single extrusion (E1), re-extrusion (E2) and extrusion with a masterbatch (MB). As reported in our previous works, the XRD pattern of Cloisite 15A (here not reported for sake of clarity) presents a main broad peak at 2.8° (the position is indicated with dotted vertical lines included in Figure 2a-2c) corresponding to a d-spacing of 3.15 nm [26,[35][36][37]. In Table 3 there are reported the values of 2% corresponding to the main diffraction peak of the XRD patterns and the respective values of interlayer distance calculated by Bragg's law.…”
Section: Results and Discussion 31 X-ray Diffractometry (Xrd)supporting
confidence: 63%
“…Moreover, the rate of decrease of M v of PLA + OM-HT is higher than that PLA+U-HT. This result is probably due to the presence of the organic modifier that could promote the degradation phenomena, as reported in the scientific literature [42]. Results derived from DSC measurements are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 52%
“…However, interfacial frictional stress caused by matrix shrinkage during the curing process may have accounted for the strengthening of the composite. In another study, Scaffaro et al 7 reported the effect of nature and content of organically modified clay on the properties of PET nanocomposites. However, the filler content used were low (3, 5 and 10 wt%) for each kind of Cloisite clay (15A and 30B), when compared to the contents used in the present study.…”
Section: Introductionmentioning
confidence: 99%